Academic Cheating: The Significance of Religion - Rosfianti M. Yadasang; Rosma Ndiak (Universitas 17 Agustus 1945 Semarang, 2023)
The role of cheating religion in academic cheating is the focus of this study. This study included 137 Fajar University Makassar students who attended lectures during the Covid-18 outbreak. In this investigation, saturated samples were used. Questionnaires were used to gather the data, which was then analyzed using path coefficient analysis using the Smart PLS tool. The result of this study is that academic pressure effects academic cheating behavior; opportunity does not influence academic cheating behavior; rationalization influences academic cheating behavior; capacity to influence academic cheating behavior; ethics According to the findings of multigroup study, religiosity is modest and reduces academic cheating, but not significantly. Religious students are more likely to avoid academic cheating while being under less pressure in terms of opportunity, talent, justification, and ethics. At Fajar University Makassar, there are several ways to prevent academic cheating, including conducting outreach activities about cheating and its consequences, informing students that cheating will be caught and announced, and ensuring that students do not work in an unsatisfactory manner. fraud, demonstrating that any fraud would be penalized, educating kids to write without cheating, and encouraging them to conduct ethically.